2009
DOI: 10.1158/0008-5472.can-09-2522
|View full text |Cite
|
Sign up to set email alerts
|

Host Lymphodepletion Enhances the Therapeutic Activity of an Oncolytic Vaccinia Virus Expressing 4-1BB Ligand

Abstract: Oncolytic viral vectors have shown promise as antitumor therapeutic agents but their effectiveness is complicated by induction of antiviral antibody responses and rapid host clearance of recombinant vectors. We developed a recombinant oncolytic vaccinia virus expressing the 4-1BBL T-cell costimulatory molecule (rV-4-1BBL) and showed modest tumor regression in the poorly immunogenic B16 murine melanoma model. To improve the therapeutic potential of this vector, we tested the antitumor activity of local intratum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 43 publications
(52 reference statements)
2
32
0
Order By: Relevance
“…For example, expression of the ligands of TNF receptor superfamily such as OX40L, 4-1BBL, and GITRL by has been demonstrated to enhance the efficacy of adenovirus and vaccinia vectors delivered intratumorally (Andarini et al, 2004;Calmels et al, 2005;Kim, Kim-Schulze, Kim, & Kaufman, 2009). Most of the studies demonstrated that such viruses could induce stronger infiltration of immune cells into the virus-injected tumors; however, the question remained whether this was merely a reflection of an enhanced antiviral immune response and whether this would translate into a more effective systemic antitumor immunity.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…For example, expression of the ligands of TNF receptor superfamily such as OX40L, 4-1BBL, and GITRL by has been demonstrated to enhance the efficacy of adenovirus and vaccinia vectors delivered intratumorally (Andarini et al, 2004;Calmels et al, 2005;Kim, Kim-Schulze, Kim, & Kaufman, 2009). Most of the studies demonstrated that such viruses could induce stronger infiltration of immune cells into the virus-injected tumors; however, the question remained whether this was merely a reflection of an enhanced antiviral immune response and whether this would translate into a more effective systemic antitumor immunity.…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…These antigen-presenting cells in turn stimulate a Th1 response, which promotes T-cell-based tumor killing. 18,19 …”
Section: Viral Selectionmentioning
confidence: 99%
“…These studies concluded that administration of naïve and early effector T cells, in combination with a lymphodepleting pretreatment regimen, g c cytokine administration, and vaccination, resulted in the eradication of established tumors (18)(19)(20). A conditioning treatment of mice (e.g., sublethal irradiation) prior to iPS cell transfer or cytokine treatment (IL-2 or IL-15) may benefit iPS cell-based therapies.…”
Section: Adoptive Transfer Of Tcr Gene-transduced Ips Cells Prevents mentioning
confidence: 99%